TEKNOLOGI DIGITAL MARKETING PRODUK UNGGULAN DAERAH MINUMAN BERBAHAN DASAR NIRA AREN PADA LABORATORIUM PEMASARAN POLITEKNIK NEGERI MANADO - Arief Perdana Kumaat (Jurusan Administrasi Bisnis Politeknik Negeri Manado, 2023)
Entrepreneurs involved in processed palm sap products in the North Sulawesi regionprimarily focus on the processed palm sap, transforming it into palm sap-based beverageproducts. The recurring issue, especially in the marketing domain, is the necessity formarketing techniques utilizing a digital approach, such as online marketing with anintegrated marketing control system. To address this issue, a more creative andinnovative solution is required, where the marketing process must enter the digital realm,in line with the penetration of nearly all segments related to the business world into thedigital realm, resulting in the digital economy. Therefore, the solution to the marketingrelated challenges faced is to implement digital marketing, also known as DigitalMarketing. In this paper, to support the sustainable and environmentally friendlydevelopment of micro, small, and medium-sized enterprises (MSMEs) producing palmsap-based beverages, a design and implementation of Digital Marketing technology forpalm sap-based beverage products as regional flagship products have been developedbased on previous research. The selected MSME partner to support the research conceptand serve as research sample is Kertina's Home Industry, with one of their products beinga branded banquet beverage called 'KELUARGA,' located in Manado City. This researchwill create a design and implementation of Digital Marketing technology for palm sapbasedregional flagship products to enhance the eco-friendly competitiveness of MSMEs. The development of this Digital Marketing technology design and implementation is carried out at the Marketing Laboratory of Manado State Polytechnic.